Co-operation and trade in food crop products in the ECOWAS sub-region - United Nations Economic Commission for Africa, Joint ECA/FAO Agricultural Division (Addis Ababa, Ethiopia : United Nations Economic Commission for Africa, Joint ECA/FAO Agriculture Division., 1980)
This book is on the co-operation and trade in food crop products in the ECOWAS Sub-Region
"January 1980."
oo 08/04/2019
Loans
Keywords: Agriculture, Cooperative; Cooperative marketing of farm produce; Produce trade